Comparativo entre los métodos multidimensional y convencional para medir el nivel de pobreza en el centro poblado Torres de San Borja - Moche 2016 - Barreto Salcedo, Neils Miguel (2016)
There are different methods for measuring poverty. In Peru, Poverty Lines are still used as a conventional method of measuring poverty. However, because the monetary aspect does not reflect all the deprivations of a family or person, the disadvantages and limitations of this method to reflect the true level of poverty are evident. Before this problem, a comparative study was carried out using two methods, the Conventional and the Multidimensional, in order to know the difference between the two in the poverty measurement of the center of Torres de San Borja-Moche, by 2016. For this purpose a survey was applied whose indicators are based on Poverty Lines (conventional method) and the Multidimensional method of Alkire & Foster. In addition, concepts are developed and data are obtained on the counting rate, adjusted gap, severity index, among other tools. It is shown that poverty measurement using the multidimensional method considers 94.55% of poverty in a sample of 55 families compared to 67.27% that determines the conventional method; Both results with a 90% confidence level. Finally, alternatives are proposed for this problem.